2004
DOI: 10.1080/00071660412331286262
|View full text |Cite
|
Sign up to set email alerts
|

Constant photoperiods and sexual maturity in broiler breeder pullets

Abstract: 1. Broiler breeder pullets were maintained on 10-, 11-, 12-, 13-, 14- or 16-h photoperiods to determine the effect of constant photoperiods on sexual development in broiler breeders. The birds were fed to achieve a 2100 g body weight at approximately 17 or 20 weeks to see if the photosexual response was modified by rate of growth. 2. In both body weight groups, pullets maintained on 10h were the first to reach sexual maturity (50 eggs/100 bird-d), and these and the 11-h pullets matured significantly earlier th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 5 publications
2
14
0
Order By: Relevance
“…This index conveniently provides an estimate of gross margin without the need for financial inputs, and can be universally applied. A regression of gross margin index on the age at 2.1 kg body weight for data from the current two trials and the experiment reported by Lewis et al (2004) revealed a curvilinear response, and showed that, to maximise gross margin in birds reared on constant stimulatory photoperiods, 2.1 kg needs to be reached between 18 and 19 weeks (Figure 8). where y = gross margin index (hatching egg numbers (n) -total feed (kg), and x = age at 2.1 kg body weight (d).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This index conveniently provides an estimate of gross margin without the need for financial inputs, and can be universally applied. A regression of gross margin index on the age at 2.1 kg body weight for data from the current two trials and the experiment reported by Lewis et al (2004) revealed a curvilinear response, and showed that, to maximise gross margin in birds reared on constant stimulatory photoperiods, 2.1 kg needs to be reached between 18 and 19 weeks (Figure 8). where y = gross margin index (hatching egg numbers (n) -total feed (kg), and x = age at 2.1 kg body weight (d).…”
Section: Discussionmentioning
confidence: 99%
“…The shaded area represents the 50 to 53 g range of egg weights regarded universally as the minimum weight for hatching egg usage The most likely explanation for the 34-d difference in ASM between accelerated and conventionally grown birds exposed to the INCA regimen, but only 22-d difference when for the INCB birds (Table 3), is a difference in the rate at which photorefractoriness was dissipated. Shorter, less stimulatory daylengths and increased feed allocations both allow broiler breeders to become photoresponsive more rapidly than birds exposed to longer photoperiods or those given stricter feed control (Lewis et al, 2004). The difference between the two INCB groups suggests that the more generous feed allocation effected a 22-d advance in ASM, and the initial eight weeks of minimally stimulatory photoperiods (< 11-h) experienced by the INCA birds, in contrast with the INCB birds that had no exposure to < 11 h daylengths, accounted for a further 12 d of advanced maturity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The length of exposure to short daylengths and the age at which birds acquire photosensitivity was previously investigated in female broiler breeders by Lewis et al (2007). Females photostimulated from 8 to 16 h light/d at 69, 76, 83 or 97 d of age did not respond to photostimulation, and dissipation of photorefractoriness was delayed so that birds matured at the same rateas if they had been maintained on long days from hatch, as the delay in ASM was similar to the delay seen in females reared on 16 h light (Lewis et al, 2004). An advance in ASM was observed when females were photostimulated at 111 and 125 d, but a bimodal distribution was observed when the females were photostimulated at 111 d, as the ASM in some had been advanced while others matured as if reared on 16 h light/d (Lewis et al, 2007), suggesting that there is some genetic variation in the acquisition of photosensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence of juvenile photorefractoriness has been found in broiler breeders reared on different constant daylengths, with the age at sexual maturity (ASM) being delayed in birds reared on long daylengths in both females (Lewis et al, 2004) and males . This suggests that photorefractoriness is dissipated at different rates, and that dissipation could occur at a faster rate when broiler breeders are exposed to short daylengths for a period of time.…”
Section: Introductionmentioning
confidence: 99%